KEARIFAN LOKAL DALAM KARYA FILM KOMUNITAS GRESIK MOVIE - Moh Mahrush Ali; Andi Taslim Saputra (Universitas Negeri makassar, 2024)
Gresik Movie is a film community from the Gresik area that accommodates young people who are interested in the world of film. This community still exists today and is more than a decade old. The films produced are also inseparable from the specificities of the region or locality. This research aims to describe film works from the Gresik Movie community that contain local wisdom. The research method used is qualitative, with data collection techniques namely observation (document review), interviews, and literature study. The data analysis technique is to examine the work of the Gresik Movie community films uploaded to their YouTube account. Interviews were also conducted with the founder of the Gresik Movie community to complete and ensure the information data was valid. Literature study to look for additional data related to this research topic, both from journal articles, books, and online media. The results of this research show that the Gresik Movie community is trying to preserve local wisdom through film works. The localities shown in Gresik Movie's films include language, location, typical food, art and culture, people, and profiles of artists. The films produced are also varied, for example, fiction films, documentaries, web series, talk show programs, and magazine shows.